On the theory of convergence and compactness for Beltrami equations - Lomako, T.V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
The convergence and compactness theorems are proved for classes of regular solutions of the Beltrami degenerate equations with restrictions of integral type on the dilatation.